The after-school sedentary behavior status among children and adolescents with intellectual disabilities - Yuan, Yaqing; Ding, Jianing; Wang, Chao; Zhang, Shaohua; Wang, Yinping; Liu, Yang; Liu, Jingmin (Frontiers in Psychiatry, 2022)
Background There is evidence that the after-school period plays an essential role in accumulating sedentary behavior (SB) among children and adolescents, as well as implementing potential interventions. However, relatively little is known regarding SB status of children and adolescents with intellectual disabilities (ID) during the after-school period. The purpose of this study was to investigate the total level and specific pattern of the after-school SB among children and adolescents with ID. Methods The after-school SB status among 325 children and adolescents with ID was evaluated by the parent-reported Children’s Leisure Activities Study Survey-Chinese edition questionnaire. Results Parents of children and adolescents with ID reported approximately 204 min/day of after-school SB. Specifically, the longest time of the after-school period was spent performing the screen-based SB (84 mins/d). This was followed by recreational SB and educational SB (50 and 30 mins/d, respectively). The children aged 6–12 years old engaged more time in recreational SB than adolescents aged 16–18 years old (p < 0.05) during the after-school period. Further, the data indicated that 37.5% of children and adolescents with ID achieved the guideline limitation of 2-h-maximum screen-based SB during the after-school hour. Conclusion Children and adolescents with ID spent a large portion of the after-school period in SB, particularly engaged in more time on after-school screen-based SB. Future efforts should focus on developing and implementing period-specific interventions designed to reduce after-school SB in the segment of this population.